2017
DOI: 10.1177/1367006916688333
|View full text |Cite
|
Sign up to set email alerts
|

Aiming at the same target: A masked priming study directly comparing derivation and inflection in the second language

Abstract: Aims and objectives/purpose/research questions: We compared the processing of morphologically complex derived vs. inflected forms in native speakers of German and highly proficient native Russian second language (L2) learners of German. Design/methodology/approach: We measured morphological priming effects for derived and inflected German words. To ensure that priming effects were genuinely morphological, the design also contained semantic and orthographic control conditions. Data and analysis: 40 native speak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 32 publications
(38 reference statements)
5
43
0
Order By: Relevance
“…In the present study, we found significant morphological priming effects for both L1 and L2 speakers of German and for different types of derived words. This finding is in line with results from previous masked priming studies for (suffixed) derived word forms in a variety of languages, including English (Silva & Clahsen, ), German (Jacob et al., ), Turkish (Kirkici & Clahsen, ), and extends them to derivation by prefixation. Furthermore, in line with previous L1 research, morphological priming in both L1 and L2 speakers was clearly dissociable from facilitation due to orthographic or semantic prime–target overlap (Rastle et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, we found significant morphological priming effects for both L1 and L2 speakers of German and for different types of derived words. This finding is in line with results from previous masked priming studies for (suffixed) derived word forms in a variety of languages, including English (Silva & Clahsen, ), German (Jacob et al., ), Turkish (Kirkici & Clahsen, ), and extends them to derivation by prefixation. Furthermore, in line with previous L1 research, morphological priming in both L1 and L2 speakers was clearly dissociable from facilitation due to orthographic or semantic prime–target overlap (Rastle et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…For L1 speakers, morphological priming effects indicative of stem–affix decomposition were found to be reduced for irregular (relative to regular) inflected words, even for irregular forms that have segmentable affixes/morphemes (Jacob, Fleischhauer, & Clahsen, ; Neubauer & Clahsen, ; Sonnenstuhl, Eisenbeiss, & Clahsen, ). For L2 speakers, a number of masked priming studies that directly compared derivation and inflection (Jacob et al., ; Kirkici & Clahsen, ; Silva & Clahsen, ) found efficient priming effects for derivation, but reduced or no priming for regular inflection in the same speakers. In contrast, other L2 studies reported significant priming effects for inflected words (Feldman et al., ; Foote, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…significant priming effects with both types of primes (e.g. Jacob et al, 2018). However, the language status of written Setswana may also affect priming from suffixed inflected words, possibly yielding reduced or no priming effects for our speakers in such cases, as shown by previous studies on late bilinguals (Kirkici & Clahsen, 2013;Silva & Clahsen, 2008).…”
Section: The Present Studymentioning
confidence: 52%